El delito de desaparición forzada de personas en América Latina - Isaac Marcelo Basaure Miranda (Ius Humani. Jornal do direito, 2018)
The objective of this paper is to determine the origin of the crime of forced disappearance of people in Latin America. The methodology used to carry out the research consisted in the normative, historical and jurisprudential analysis that exists internationally in the subject under study, using the analytical theoretical method. The structure of the article begins with a review of the historical evolution that said criminal behavior has had in the region. Then the most relevant precedents of the Inter-American Court of Human Rights in the matter are examined, in order to identify their main interpretative standards; as well as its reception in the Inter-American Convention on Forced Disappearance of Persons, and in the main international treaties and declarations on Human Rights. The essay concludes with a study of the recent impact of the judgments of the Inter-American Court of Human Rights on the Forced Disappearance of Persons. Finally, we conclude that the aforementioned crime began to be practiced in Guatemala, in 1966, and, from there, to expand to the rest of Latin America.